Medical and geographical determinants of oncopathology in the population - M. P. Hrebniak; O. V. Kirsanova; V. V. Taranov; N. H. Mikriukova (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2021)
The aim: to study the permanent risk factor of oncopathology in order to determine its medical and geographical features and assess their impact on oncopathology of the population of Zaporizhzhia region.